2008
DOI: 10.1044/0161-1461(2008/008)
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Examination of Current Guidelines for Evidence-Based Practice in Child Language Intervention

Abstract: EBP is a necessary part of effective and ethical treatment. The resources needed, time involved, and availability of relevant information make current guidelines for EBP challenging for most full-time practitioners. Specific recommendations to address these concerns are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 33 publications
(41 reference statements)
0
12
0
2
Order By: Relevance
“…Their reviews, pertaining to behavioral, social, health, and educational interventions, are indexed in MEDLINE (Clark, 2007). However, these organizational resources may be of limited value for issues pertaining to speech and language interventions primarily due to their focus on randomized controlled trials that are not typically employed with children (Brackenbury, Burroughs, & Hewitt, 2008), and they require a paid subscription. The Centre for Reviews and Dissemination (CRD) provides an international database of systematic reviews on health care interventions; this rapidly growing collection of systematic reviews is freely accessible to the public.…”
Section: Meta-analytic Review Of the Literaturementioning
confidence: 99%
“…Their reviews, pertaining to behavioral, social, health, and educational interventions, are indexed in MEDLINE (Clark, 2007). However, these organizational resources may be of limited value for issues pertaining to speech and language interventions primarily due to their focus on randomized controlled trials that are not typically employed with children (Brackenbury, Burroughs, & Hewitt, 2008), and they require a paid subscription. The Centre for Reviews and Dissemination (CRD) provides an international database of systematic reviews on health care interventions; this rapidly growing collection of systematic reviews is freely accessible to the public.…”
Section: Meta-analytic Review Of the Literaturementioning
confidence: 99%
“…He stated that clinicians have a responsibility ''to evaluate the literature and choose management procedures that have a credible evidence base.'' However, many clinicians state that a lack of time and access to appropriate materials interfere with their ability to use current research to guide clinical practice (Brackenbury et al; 22 Zipoli and Kennedy 21 ). Several researchers have offered suggestions to attempt to circumvent those issues.…”
Section: Why the Disconnect?mentioning
confidence: 99%
“…Zipoli and Kennedy 21 further suggested that ASHA make available clinical practice guidelines and reviews that summarize the evidence on topics related to clinical practice. Brackenbury et al 22 also provided a variety of ideas to help clinicians access efficiently and evaluate pertinent information related to clinical practice. Although all of those recommendations may make it easier for clinicians to obtain information, it is ultimately their responsibility to use that information as appropriate in their own clinical practice.…”
Section: Why the Disconnect?mentioning
confidence: 99%
“…While scholars have gone to great lengths to illustrate the value of qualitative research and ensure that it is well-represented in all areas of academic life, there remains a gap of equality when compared to quantitative research, which is still viewed by many as superior, specifically in applied fields such as health (Brackenbury Burroughs, & Hewitt, 2008;Estabrooks, 1998). This has become particularly true as the evidence-based movement has continued to find its way into discussions around the legitimacy of qualitative research and resulted in calls for making qualitative research 'more scientific' and 'disciplined' (Lather, 2013), which has somewhat contentiously resulted in some more positivist ways of thinking about qualitative methods (St. Pierre, in press).…”
Section: Arguments From the Bottom Of The Pyramidmentioning
confidence: 99%